2022
DOI: 10.1038/s41467-022-29240-5
|View full text |Cite
|
Sign up to set email alerts
|

cAMP and c-di-GMP synergistically support biofilm maintenance through the direct interaction of their effectors

Abstract: Nucleotide second messengers, such as cAMP and c-di-GMP, regulate many physiological processes in bacteria, including biofilm formation. There is evidence of cross-talk between pathways mediated by c-di-GMP and those mediated by the cAMP receptor protein (CRP), but the mechanisms are often unclear. Here, we show that cAMP-CRP modulates biofilm maintenance in Shewanella putrefaciens not only via its known effects on gene transcription, but also through direct interaction with a putative c-di-GMP effector on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…The cytosolic c-di-GMP measurement was performed as previously described [ 21 ]. Briefly, they were grown in 24-well plate, in the presence of 0.02% Citrox BCL, and collected for up to 24 h. Moreover, a co-culture experiment of L. pneumophila SG68703154 with A549 cells and 0.02% Citrox BCL was set up and supernatant bacteria were harvested by centrifugation at 13,000 g after 24 h. Samples were collected for analysis at 3, 9, 15 and 24 h. The centrifugation was performed at 13,000 g for 2 min and at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The cytosolic c-di-GMP measurement was performed as previously described [ 21 ]. Briefly, they were grown in 24-well plate, in the presence of 0.02% Citrox BCL, and collected for up to 24 h. Moreover, a co-culture experiment of L. pneumophila SG68703154 with A549 cells and 0.02% Citrox BCL was set up and supernatant bacteria were harvested by centrifugation at 13,000 g after 24 h. Samples were collected for analysis at 3, 9, 15 and 24 h. The centrifugation was performed at 13,000 g for 2 min and at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al confirmed that nucleotide second messengers (such as cyclic adenosine monophosphate (cAMP) and cyclic diguanylate (c-di-GMP)) play an important role in regulating biofilm maintenance. It has been reported that pathogenic bacteria have evolved strategies to manipulate host cAMP concentrations [ 75 ]. This discovery provided an important direction for new drug design.…”
Section: Strategies Of Targeting Initial Adhesion Stagementioning
confidence: 99%
“…Most DGCs and PDEs have transmembrane helix structures which can sense various input signals such as oxygen, light, antibiotics (17), and temperature (24) to regulate the level of c-di-GMP. Previous studies (25, 26) have shown that the intracellular level of c-di-GMP can regulate the conversion between the planktonic state and biofilm state of bacteria. In addition, c-di-GMP can regulate the activity of flagella to control the movement ability of bacteria and then regulate bacterial adhesion, and also regulate the synthesis of extracellular polysaccharides and extracellular proteins to promote the formation of biofilm (25).…”
Section: Introductionmentioning
confidence: 97%